Commissioner Board Monitoring to Create Firm Performance through Environmentally Friendly Management - UTOMO, Mohamad Nur; WAHYUDI, Sugeng; MUHARAM, Harjum; SIANTURI, Jeudi Agustina T.P. (Journal of Environmental Management and Tourism, 2018)
The paper is written as an empirical test on the indirect effect of Commissioner Board Monitoring on firm performance through environmental performance as mediation variable. Research sample is non-financial firms that participate into Performance Assessment Program (PROPER) and that also list at Indonesian Stock Exchange. Commissioner Board Monitoring consists of few attributes such as: Commissioner Board Size, Independent Commissioner Board, and Commissioner Board’s Frequency of Meeting. Environmental performance is measured with the use of PROPER by the Ministry of Life Environment and Forestry for Indonesian Republic. Firm performance is proxied with Return on Asset (ROA) and Tobin’s Q. Research gains some results. Commissioner Board Monitoring has a positive effect on both environmental performance and firm performance. Environmental performance has a positive effect on firm performance. Commissioner Board Size has an indirect effect on firm performance through environmental performance. All these findings support agency theory and stakeholder theory. Any firms attempting to maximize performance shall balance the interest of shareholder (firm owner) and stakeholder.